1994
DOI: 10.1159/000227343
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Argyrophilic Nucleolar Organizer Staining for Predicting Prognosis of Patients with Recurrent Soft Tissue Sarcoma

Abstract: Local recurrence of tumor is a common phenomenon in soft tissue sarcoma (STS) and may be accompanied by an increase in malignant potential. In the present study, an increase of proliferative activity in recurrent tumors compared to primary tumors was observed using a silver stain for nucleolar organizer regions (AgNOR), and its implication for predicting prognosis is assessed. 44 patients with STS showing local tumor recurrence were selected. Local recurrence was defined as new tumor growth more than 2 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(9 reference statements)
0
7
0
1
Order By: Relevance
“…The validity of clinicopathologic and molecular genetic variables in predicting outcome of SS is still under evaluation. Among other parameters, primary tumor size, margin of resection, mean mitotic activity, DNA ploidy, and proliferative index have been proposed as prognostic factors for survival in SS 27, 42–44…”
Section: Discussionmentioning
confidence: 99%
“…The validity of clinicopathologic and molecular genetic variables in predicting outcome of SS is still under evaluation. Among other parameters, primary tumor size, margin of resection, mean mitotic activity, DNA ploidy, and proliferative index have been proposed as prognostic factors for survival in SS 27, 42–44…”
Section: Discussionmentioning
confidence: 99%
“…The retroperitoneum is an adverse site of origin with a 5-year survival rate of only 14% probably due to late diagnosis and difficult surgical accessibility [1,6,9,10]. Local recurrence may be accompanied by an increased malignant potential and is considered to be a risk marker for distant failure [4,11,12]. Cases 1 and 2 shared almost all the adverse prognostic criteria recently established in a multicenter series of 216 patients [1]: age older than 50 years; tumor size 18 cm, and a deeply invading high-grade nonmyxoid tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies on bone and soft tissue tumors, the relationship of various growth indices to prognosis has been examined: those were labeling rates with BrdU [10,11], Ki-67 [30], PCNA [2,3] and argyrophilic nucleolar organizer region (AgNOR) [12,13,28], mast cell count in tumors [29], and DNA ploidy pattern [14]. Retrospective studies reported close correlation of AgNOR, Ki-67, DNA ploidy pattern and mast cell count with prognosis and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…No reflection of heterogeneity that is a characteristic of bone and soft tissue tumors is also a demerit of this method. AgNOR has been reported to be useful as a prognostic indicator [12,13,28]. Although a merit of AgNOR is possible treatment of many tumor tissues, the function of AgNOR itself is not clarified yet and theoretical background is obscure even though empirically right.…”
Section: Discussionmentioning
confidence: 99%